Extrapulmonary Tuberculosis Leading to Abdominal Wall Mass in Young Patient - Mohadeseh Karimi; Ali AtashAbParvar (Case Reports in Infectious Diseases)
Background. Tuberculosis is a bacterial infection that is caused by Mycobacterium tuberculosis. Tuberculosis has arguably been the largest killer of humans historically, and it remains one of the most important infectious causes of death in the world. Tuberculosis can be classified into different forms and it manifests as pulmonary and out pulmonary, respectively, in 85% and 15% of cases. Only a few cases of tuberculosis with abdominal wall involvement have been reported. Case Presentation. Herein, we present a 27-year-old Persian woman, presented with asymmetric abdominal bulging in the right side of the periumbilical area since 6 months before admission that has no pain or secretion. The patient was oriented and not ill or toxic in general appearance. Vital signs were within normal ranges. An abdominal physical examination revealed a mobile, well-bordered, nontender mass 3 × 3 centimeter (cm) in diameter palpated in the right periumbilical area. The patient underwent surgery which revealed a cystic lesion that was carefully resected. In histopathology examination of the specimen resection, tuberculosis was confirmed. Conclusion. We report a rare case of extrapulmonary tuberculosis that was identified at the abdominal wall. Due to the high number of cases of TB and the development of extrapulmonary forms that can present in an unusual location as an abdominal wall which are difficult to diagnose, it is very important to keep in mind the differential diagnosis of tuberculosis.